(untitled) (International Journal of Engineering and Computer Science, 2014)
this paper implements and enhances performance of software random testing. Random testing is a base software testing technique that can be used to improve the software reliability as well as to discover software failures. Random testing is a black-box software testing technique where programs are tested by generating random, independent inputs. In proposed methods uses both Monte Carlo and Las Vegas Randomized algorithms. Monte Carlo has fast execution while Las Vegas has low execution time, but sometimes Monte Carlo algorithm gives false result while Las Vegas gives always correct result. In proposed method has two result sets, in first result set has executed test cases and in second has fails test cases. Initially test cases are tested using Monte Carlo algorithm and produced executed and fail result sets. The fail result set is again tested using Las Vegas algorithm because sometimes Monte Carlo gives false result. We present a technique that improves performance random testing. These results are very hopeful, given that evidences that our perception is likely to be useful in improving the efficiency of random testing